PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA DALAM PEMBELAJARAN BIOLOGI KELAS XI IPA SMAN 4 PEKANBARU TAHUN AJARAN 2013/2014 - Weni Harnisa Misdana; Yustina Yustina; R. Hussien Arief (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrak : The aim of this study was to determine the application of the learning model of Problem-Based Learning (PBL) to improve higher order thinking skills of students in learning biology class XI SMA Negeri 4 Pekanbaru in Academic Year 2013/2014. Research was conducted in May 2014 with sample student is XI IPA 1 and XI IPA 4 SMA Negeri 4 Pekanbaru. This research is an experiment with a class XI IPA 4 as the experiment class and XI IPA 1 as the control class. The parameters used in the study of high of thinking skills (C4 (Analysis), C5 (Evaluate), and C6 (Create). The result of high of thinking skills can be seen from the tests given to students in grade experiment that is equal to 72,34 with enough category, while the control class at 60,08 with less category. Based on research that has been done, the model Problem Based Learning (PBL) in learning biology showed better results in terms of higher order thinking skills students class XI IPA SMAN 4 Pekanbaru in Academic Year 2013/2014.Key words: high school senior, problem-based learning, higher order thinking skills